The Collaborative Experience of Value Chain Architecture: A Systemic Paradigm to Building Customer Loyalty (Global Journal of Management and Business Research, 2011)
In most industries, customer retention has replaced the aggressive and offensive customer attraction ideals of transactional marketing. Collaborative architecture within the value chain represents such shift from marketing mix approach to Relationship Marketing, which though lacks knowledge of its own but spans inter-firm alignments to reform marketing activities via debunking selfishness, superficiality and self-indulgence. Traditional marketing management theories focus on oppressive associations, relationship between customer and product, short-term or even single exchange(s), offensive marketing and/or power-based notions whereas relational interactions change conflicts to harmonic co-operation, associations, and connections, and ultimately infrequent business relationships to on-going. The economic soundness of such mutual participative architecture revolves on strategic optimization that serves the interests of stakeholders on the grounds that customer retention and customer loyalty reflect complex activity involving inputs from vendors and other independent firms and continues even by the manner the dealers handle and explain customer complaints and doubts. All the steps from design to after-sales service are mutually integrated flows aimed at reducing marketing expenses; increasing customer switching costs; and moving the customer up, in a co-ordinated manner, to viral level of customer loyalty ladder. Whether in full-fat and semi-skimmed innovations, the implication is that customer satisfaction is a value-chain and systems activity built on trust, mutuality, promise, shared values, and commitment, whereby each subsystem interacts mutually with others to maintain the wholes of customer satisfaction and profitability.
Keywords: collaboration; value chain; paradigmatic shift; participative architectures; relationship marketing; customer retention; marketing management